2020
DOI: 10.3390/nu12040951
|View full text |Cite
|
Sign up to set email alerts
|

Oral Supplementation of Sodium Butyrate Attenuates the Progression of Non-Alcoholic Steatohepatitis

Abstract: Sodium butyrate (SoB) supplementation has been suggested to attenuate the development of non-alcoholic fatty liver disease (NAFLD). Here, we determined the therapeutic potential of SoB on NAFLD progression and molecular mechanism involved. Eight-week old C57BL/6J mice were pair-fed a fat-, fructose- and cholesterol-rich diet (FFC) or control diet (C). After 8 weeks, some mice received 0.6g SoB/kg bw in their respective diets (C+SoB; FFC+SoB) or were maintained on C or FFC for the next 5 weeks of feeding. Liver… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
46
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 53 publications
2
46
0
1
Order By: Relevance
“…Mice in the WD and WD-GP-groups consumed on average 0.3–0.4 g butyric acid /kg BW per day. Oral supplementation of butyrate has been reported to be protective against both NAFLD ( 72 ) and insulin resistance ( 73 ), yet increased levels of butyrate-producing bacteria and levels in feces has also been linked to these diseases ( 23 25 , 27 29 ). Providing dietary butyric acid in butterfat may have protected mice fed WD and WD-GP against hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Mice in the WD and WD-GP-groups consumed on average 0.3–0.4 g butyric acid /kg BW per day. Oral supplementation of butyrate has been reported to be protective against both NAFLD ( 72 ) and insulin resistance ( 73 ), yet increased levels of butyrate-producing bacteria and levels in feces has also been linked to these diseases ( 23 25 , 27 29 ). Providing dietary butyric acid in butterfat may have protected mice fed WD and WD-GP against hyperglycemia.…”
Section: Discussionmentioning
confidence: 99%
“…Experimental setup used in the present study and sample size calculations were based on previous studies of our group [25]. Indeed, in these studies, it was shown that in this feeding model, 5 weeks of treatment with a compound/ oil are sufficient to show 'therapeutic´efficacy [25,29]. For the first 8 weeks of the experiment, animals were either fed a liquid control diet (C; 69E% carbohydrates, 12E% fat derived from soybean oil, 19E% protein; Ssniff, Soest, Germany) or a liquid butterfat-, fructose-and cholesterol-rich diet (BFC; 60E% carbohydrates, 25E% fat derived from butterfat, 15E% protein, 50% wt/wt fructose and 0.16% wt/wt cholesterol; Ssniff, Soest, Germany).…”
Section: Animals and Feedingmentioning
confidence: 98%
“…Overall, supplementation of sodium butyrate has been shown to prevent simple steatosis progression to steatohepatitis through various mechanisms [ 43 ]. Acetate and propionate also have anti-inflammatory effect, however, these two SCFAs can promote lipid accumulation and gluconeogenesis in the liver [ 44 ], therefore, they are unlikely to be used for NAFLD therapy.…”
Section: Gut Microbiota Metabolites In the Pathogenesis Of Nafldmentioning
confidence: 99%